“To see a world in a grain of sand”:: Towards Future-Oriented What-If Analysis in Narrative Research - Sools, Anneke (Narrative Matters)

(untitled) (The University of New Brunswick, 2012)
In this article, I explore narrative building blocks for future-oriented what-if (i.e., possibilities-generating) analysis developed in a health promotion study. The aim of this study was to gain insight into future possibilities for good health among participants known for their poor health status. In narrative inquiry, imagining future possibilities and prospective temporal orientation are seldom regarded as interesting for their own sake, despite ample attention to the role of temporality. The methodological reflection in this article is complemented with a discussion of ethical issues (regarding authorship and representation) in the proposed method of analysis.